Perceptions of stigma among people with lived experience of methamphetamine use within the hospital setting: qualitative point-in-time interviews and thematic analyses of experiences - Forchuk, Cheryl; Serrato, Jonathan; Scott, Leanne (Frontiers in Public Health, 2024)
Objectives As part of a larger mixed-methods study into harm reduction in the hospital setting and people with lived experience of methamphetamine use, stigma was found to be a prominent issue. The aim of this secondary analysis was to investigate the issue of stigma. Design Participants completed a one-time qualitative interview component to assess their experiences in the hospital setting. Setting The study setting included secondary and tertiary care in Southwestern Ontario, Canada. Participants who had received care from these settings were also recruited from an overdose prevention site, a primary healthcare center, a national mental health organization, an affordable housing agency, and six homeless-serving agencies between October 2020 and April 2021. Participants A total of 104 individuals completed the qualitative component of a mixed-methods interview. Sixty-seven participants identified as male, thirty-six identified as female, and one identified as non-binary. Inclusion criteria included past or current use of methamphetamine, having received services from a hospital, and being able to communicate in English. Methods Open-ended questions regarding experiences in the hospital setting were asked in relation to the lived experience of methamphetamine. A secondary analysis was conducted post-hoc using a thematic ethnographic approach due to prominent perceptions of stigma. Results Three themes were identified. The first theme identified that substance use was perceived as a moral and personal choice; the second theme pertained to social stigmas such as income, housing and substance use, and consequences such as being shunned or feeling less worthy than the general patient population; and the third theme highlighted health consequences such as inadequate treatment or pain management. Conclusion This study revealed that stigma can have consequences that extend beyond the therapeutic relationship and into the healthcare of the individual. Additional training and education for healthcare providers represents a key intervention to ensure care is non-stigmatizing and patient-centered, as well as changing hospital culture.